Improving global paleogeography since the late Paleozoic using paleobiology - W. Cao; S. Zahirovic; N. Flament; N. Flament; S. Williams; J. Golonka; R. D. Müller; R. D. Müller (Biogeosciences, 2017)
Paleogeographic reconstructions are important to understand Earth's tectonic evolution, past eustatic and regional sea level change, paleoclimate and ocean circulation, deep Earth resources and to constrain and interpret the dynamic topography predicted by mantle convection models. Global paleogeographic maps have been compiled and published, but they are generally presented as static maps with varying map projections, different time intervals represented by the maps and different plate motion models that underlie the paleogeographic reconstructions. This makes it difficult to convert the maps into a digital form and link them to alternative digital plate tectonic reconstructions. To address this limitation, we develop a workflow to restore global paleogeographic maps to their present-day coordinates and enable them to be linked to a different tectonic reconstruction. We use marine fossil collections from the Paleobiology Database to identify inconsistencies between their indicative paleoenvironments and published paleogeographic maps, and revise the locations of inferred paleo-coastlines that represent the estimated maximum transgression surfaces by resolving these inconsistencies. As a result, the consistency ratio between the paleogeography and the paleoenvironments indicated by the marine fossil collections is increased from an average of 75 % to nearly full consistency (100 %). The paleogeography in the main regions of North America, South America, Europe and Africa is significantly revised, especially in the Late Carboniferous, Middle Permian, Triassic, Jurassic, Late Cretaceous and most of the Cenozoic. The global flooded continental areas since the Early Devonian calculated from the revised paleogeography in this study are generally consistent with results derived from other paleoenvironment and paleo-lithofacies data and with the strontium isotope record in marine carbonates. We also estimate the terrestrial areal change over time associated with transferring reconstruction, filling gaps and modifying the paleogeographic geometries based on the paleobiology test. This indicates that the variation of the underlying plate reconstruction is the main factor that contributes to the terrestrial areal change, and the effect of revising paleogeographic geometries based on paleobiology is secondary.